Economics of natural resources and the environment - Pearce, David W. (Harvester Wheatsheaf, 1990)
Concern for the environment and depletion of the earth's natural resources is at top of the political agenda in the eraly 1990s, the book provides a thorough grounding in the economics required to understand national, international and global environmental problems. It deals with the orthodox theories of the economics of polultion and optimal depletion rates fo natural resources. It also provides innovatory chapters on environmental ethics, pollution control policy in 'free' and mixed market economies and in centrally planned countries and the much discussed concept of 'substainable development'